Isomeric cross section ratio for the (n,2n) reaction on Sc-45 from 13.6 to 14.9 MeV - Bostan, M; Erduran, MN; Sirin, M; Subasi, M (AMER PHYSICAL SOC, 1997)
The isomeric cross section ratio sigma(m)/sigma(g) for the reaction Sc-45(n,2n) Sc-44(m,g) was measured in the neutron energy range of 13.6-14.9 MeV for six different neutron energies. The neutrons were produced by the H-3(d,n)He-4 reaction utilizing a SAMES T-400 neutron generator. Isomeric cross section ratios were determined by applying the method of least squares to the time behavior of the ground-state decay of isomeric pair. The absolute cross section for the formation of the metastable state was measured by the usual activation technique. The ground-state cross section was then obtained by using the absolute truss section of the metastable state and isomeric cross section ratio for each neutron energy. Experimental cross section values and isomeric cross section ratios were compared with those obtained by a statistical model calculation.
Keywords: NEUTRON; Physics